No Shipping Fees or Free Shipping? Impact of Temporal Proximity on the Relative Effectiveness of Promotional Framing - Kulkarni, Atul A. (Journal of Promotion Management, 2020)
In this research, we find that the relative effectiveness of framing a shipping promotion as “no shipping fees” versus “free shipping” may depend on temporal proximity of the promotional offer. Our findings suggest that when the promotion is on offer in immediate future, framing it as no shipping fees is relatively more effective. In contrast, when the promotion is on offer in relatively distant future, framing is as free shipping is relatively more effective. Our findings also suggest that these differences in the relative effectiveness of the two framing types may be subject to the degree of elaboration. The differences may manifest when consumers process promotional information cursorily but may dissipate when consumers elaborate more. When primed to process information cursorily, participants in our studies (Studies 1 and 2) reported higher offer evaluations and purchase intentions when (i) an ongoing promotion was framed as no shipping fees or (ii) a promotion available in the future was framed as free shipping. These effects dissipated when either the participants were primed to elaborate more (Study 3) or when the temporal aspect was eliminated (Study 4).
Keywords: dept.mrk; evaluation; framing; free shipping; peer-reviewed; promotions; temporal distance

Shopper Search in Response to Conditional Promotions: A Function of Basket Sizes and Incentive Types - Kulkarni, Atul; Yuan, Hong (Psychology and Marketing, 2025)
Keywords: Advertising; Business; Computer science; Consumer Attitudes; Consumer Behavior; Economics; Function (biology); Incentive; Incentives; Mathematics; Microeconomics; Shopping; dept.mrk; peer-reviewed